La dramaturgia musical en el litoral. Una propuesta de estudio internacional - Cetrangolo, Aníbal (Universidad Nacional del Litoral, 2019)
In this text, we propose a comparative study of the musical theatrical activity of the «littoral region» of Argentina. Given the lyrical object of our study, we will attempt an interdisciplinary analysis that will include the craft of musicians, writers, visual artists and artisans with very specific professions. Likewise, we will study the migrations in Argentina around the end of the nineteenth century and the beginning of the twentieth century. The recording of the history of the opera in upstate areas of the country is, unfortunately, circumscribed to (with a few exceptions) the forms of circumstantial chronicles motivated by the opening of some new theatre. These theatre archives are however exiguous since theatre programs and information regarding the casts were not preserved systematically and the theatres did not really produce shows but rather hosted visiting theatre companies. The very few surviving documents attest to the existence and the members of these companies, hence, the importance of studying periodic publications. The study of these materials is vital to reconstruct the past and we gather this can be achieved by comparing data coming from different playhouses, which could in turn help guesstimate the itineraries of the aforementioned theatre companies. Similarly, to carry out scientific research on this issue and to learn about the real incidence of these theatrical productions, it is also necessary to draw a comparison between documents descriptive of nearby theatres with data pertaining to playhouses located in outer areas, that is, Buenos Aires and other parts of Argentina. This said, we hereby describe the configuration of adatabase that has been in active use for decades on these very complexities and the incorporation of new data regarding theatres from the «littoral region» of Argentina.